Organizational positioning and planning of sustainability initiatives: Logic and differentiators. Issue 7 (18th June 2018) - Rodriguez, Rocio; Svensson, Göran; Eriksson, David
Abstract : Purpose: The purpose of this paper is to examine the logic and differentiators of organizational positioning and planning of sustainability initiatives between private and public organizations in the healthcare industry. Sustainability initiatives refer to organizations' economic, social and environmental actions. Design/methodology/approach: This study is based on an inductive approach judgmental sampling and in-depth interviews of executives at private and public hospitals in Spain have been used. Data were collected from the directors of communication at private hospitals, and from the executive in charge of corporate social responsibility in public hospitals. An empirical discourse analysis is used. Findings: The positioning and planning of sustainability initiatives differs between private and public hospitals. The former consider sustainability as an option that is required mainly for social reasons, a bottom-up positioning and planning. It emerges merely spontaneously within the organization, while the sustainability initiatives in public hospitals are compulsory. They are imposed by the healthcare system within which the public hospital, operates and constitutes a top-down positioning and planning that is structured to accomplish set sustainability goals. Research limitations/implications: A limitation of this study is that it is undertaken exclusively in Spanish organizations from one industry. This study differs from previous ones in terms of exploring the positioning and planning of the sustainability initiatives, which focus on the organizational logic of such sustainability initiatives. There are both common denominators and differentiators between private and public hospitals. Practical implications: The logic of determining the positioning and planning of the sustainability initiatives is mainly about satisfying organizational needs and societal demands. Nowadays, organizations tend to engage in sustainability initiatives, so it is essential to understand the logic of how organizations position and plan such efforts. Originality/value: This study investigates the path that follows sustainability initiatives in public and private organizations. It reports mainly differentiators between private and public organizations. It also contributes to explaining the organizational reasoning as to why companies make decisions about sustainability initiatives, an issue which has not been addressed sufficiently in existing theory studies.